2012
DOI: 10.1159/000335573
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Effects of Zinc and Fluoride on Caries Lesion Remineralization

Abstract: The present mechanistic in vitro study aimed to investigate dose-response effects of zinc and fluoride on caries lesion remineralization and subsequent protection from demineralization. Artificial caries lesions were created using a methylcellulose acid gel system. Lesions were remineralized for 2 weeks using citrate-containing artificial saliva which was supplemented with zinc (0–153 µmol/l) and fluoride (1.1 or 52.6 µmol/l) in a 7 × 2 factorial design. Lesions were also remineralized in the absence of zinc a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…The rationale behind using ZnF 2 was that Zn compounds, such as ZnCl2 and zinc acetate, were studied as a combination to lower fluoride concentration in NaF and were surprisingly found to promote lesion remineralization 24,25) by acting as a mineral regulator to control the porosity at the lesion surface. It was of interest to include fluoride and zinc together because they are both powerful elements for remineralization.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind using ZnF 2 was that Zn compounds, such as ZnCl2 and zinc acetate, were studied as a combination to lower fluoride concentration in NaF and were surprisingly found to promote lesion remineralization 24,25) by acting as a mineral regulator to control the porosity at the lesion surface. It was of interest to include fluoride and zinc together because they are both powerful elements for remineralization.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that this concentration can increase the remineralisation of subsurface lesions, by retarding fluoride-induced lesion arrest and increasing lesion consolidation [Lynch et al, 2011]. However, Lippert [2012] reported that the effect is dependent on relatively high fluoride concentrations, and high Zn 2+ concentrations can reduce remineralisation. While data from caries clinical trials suggest that Zn 2+ has no net effect on caries reductions resulting from the use of fluoride toothpastes [Stephen et al, 1988;Ripa et al, 1990], it seems unlikely that any effect on demineralisation exactly outweighs any possible effect on remineralisation, and that caries status risk should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc ions are commonly added to toothpaste formulations to reduce malodour by chemically binding to volatile odour molecules [12,13] and by inhibiting malodour-generating plaque bacteria [14]. Zinc has an affinity for enamel surfaces via binding to surface phosphate groups and so also has the potential to interfere with fluoride's action against caries [15,16]. Since a further benefit of use of zinc toothpastes is a reduction in calculus formation [17] via inhibition of formation of apatites and their precursors [18], it has the potential to interfere with enamel remineralisation.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Since a further benefit of use of zinc toothpastes is a reduction in calculus formation [17] via inhibition of formation of apatites and their precursors [18], it has the potential to interfere with enamel remineralisation. In vitro mechanistic studies have demonstrated the potential for this to occur in both a positive and negative fashion [15,16]. Furthermore, like phytate, zinc may offer its own protection against demineralisation.…”
Section: A C C E P T E Dmentioning
confidence: 99%